The Possibilities of the Actual Orientation of the Green Building in Iraq - Abdalqadir, Narmeen A. (PROSPECTIVE RESEARCHES, 2024)
This research covers the zone between Iraq and Iran. The ﬁrst investigated region is the 'Mesopotamian Marshes' or Iraqi-Iran Marshes, it's a wetland zone located in southern Iraq and partly in southwestern Iran. The other region is a desert district which includes a prominent part of the southern and western parts of Iraq and part of Iran. The last is the center city of Basra. The building materials were the most important building element that affected the conformation of vernacular habitats In this study, we needed to focus on the effects of ecological and energy-efficiency processes in creating vernacular habitats and the selection of optimal building systems and materials in this part of the world which can be an essential point for sustainable environmental building processes in the future. Reeds, clay, straw, bricks, and wood were the most popular building materials used by builders from this region. The impact of building material on the environment embodies the essential method implicitly signiﬁcant in this research to effectively determine traditional building materials in the environment in addition to comparative analysis which presents an essential factor of our analysis in addition to the impact of environments on building systems. The main target of this study is to beneﬁt designers and building engineers in their pursuit to ﬁnd optimal and competent solutions suitable for speciﬁc local microclimates using traditional methods in the design process that are sustainable and ecological.